Um novo retificador híbrido multipulsos sem a utilização de transformadores defasadores e/ou transformadores de interfase - Freitas, Luiz Carlos Gomes de (2006)
Recently, in order to improve the distribution of electrical energy, and to provide agreement with the power quality standards, especial emphasis on power quality has demanded performance improvement of rectifier structures as a front end power processor. Three-phase diode-bridge rectifiers are very popular in several industrial and rural applications, where an intermediate DC link provides energy for other electronic circuits. However, such standard diode-bridge rectifiers do not meet harmonic current content restrictions, as imposed by several international standards such as IEC 61000-3-4 and IEEE 519-1992. Thus, expensive and bulky passive filters or complex power factor correction and active filter structures must be installed to compensate the inherent harmonic current distortion. Therefore, in the past few years, there has been a tremendous interest in achieving low harmonic current distortion in three-phase AC to DC converters, motivating researches of several front-end multipulse rectifiers. Several structures of multipulse rectifiers have been applied in three-phase applications for mitigation of the input current harmonic content. However, these converters need magnetic circuits such as inter-phase transformers, current balancing transformers or harmonic blocking transformers. They have complex design, are heavy, bulky, expensive and only made by special order. Besides, elimination of interphase transformers is particulary desirable when there are preexisting harmonic voltages in the three-phase power source, because those harmonic voltages cause changes in the DC output leading to further complication in the design of interphase transformers. Therefore, in this thesis, controlled rectifiers operating in parallel to standard threephase diode-bridge rectifier are proposed in contrast to expensive and complex schemes, as long as the overall converter behave as a current source controlled with a suitable strategy. The fundamental idea behind a front-end programmable rectifier is the imposition of a suitable input line current waveform in order to provide low THDI and high input power factor. In conclusion, this work proposes a new concept of multipulse hybrid rectifier for ultra clean power applications. This innovative programmable three-phase power factor correction hybrid multipulse power rectifier is capable to provide ultra clean power without the need of phase-shift transformers, inter-phase transformers, current balancing transformers or harmonic blocking transformers.